2018
DOI: 10.3390/ijerph15010057
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nutritional Status of Infants Living in Arsenic-Contaminated Areas in Bangladesh and Its Association with Arsenic Exposure

Abstract: Data is scarce on early life exposure to arsenic and its association with malnutrition during infancy. This study followed the nutritional status of a cohort of 120 infants from birth to 9 months of age in an arsenic contaminated area in Bangladesh. Anthropometric data was collected at 3, 6 and 9 months of the infant’s age for nutritional assessment whereas arsenic exposure level was assessed via tube well drinking water arsenic concentration at the initiation of the study. Weight and height measurements were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Since the methylation capacity is lower than that of adults, the effect of As toxicity on the growth and development of infants deserves attention. Long-term ingestion of arsenic in food or water will inhibit the immune function of infants, resulting in slow growth and development [58], weight loss and underweight [59]; some studies have found that the neurotoxicity of As will affect the intelligence of adult children, possibly by affecting acetylcholinease activity at synapses [60,61]. We need to further strengthen the monitoring of metal content in the food intake of infants and nursing mothers, and at the same time, we need to strengthen the effect of environmental arsenic pollution on the accumulation of As in food, and control the risk of As exposure from the food source.…”
Section: Discussionmentioning
confidence: 99%
“…Since the methylation capacity is lower than that of adults, the effect of As toxicity on the growth and development of infants deserves attention. Long-term ingestion of arsenic in food or water will inhibit the immune function of infants, resulting in slow growth and development [58], weight loss and underweight [59]; some studies have found that the neurotoxicity of As will affect the intelligence of adult children, possibly by affecting acetylcholinease activity at synapses [60,61]. We need to further strengthen the monitoring of metal content in the food intake of infants and nursing mothers, and at the same time, we need to strengthen the effect of environmental arsenic pollution on the accumulation of As in food, and control the risk of As exposure from the food source.…”
Section: Discussionmentioning
confidence: 99%
“…5 Early-life malnutrition, such as undernutrition of the mother during pregnancy, nonexclusive breastfeeding, inadequate supplemental feeding, and a high prevalence of enteric illnesses, as well as poor hygiene practices, result in growth restriction in children. [6][7][8] Stunting is increasingly recognized as a major global health concern, with various high-profile projects such as Scaling Up Nutrition, the Zero Hunger Challenge, and the Nutrition for Growth Summit focusing on it. Stunting is also at the heart of the World Health Assembly's six global nutrition targets for 2025, and it has been proposed as a leading indicator for the post-2015 development agenda.…”
Section: Introductionmentioning
confidence: 99%